First Records of Coquillettidia (Coquillettidia) richiardii and Culex (Culex) perexiguus/univittatus (Diptera: Culicidae) Mosquitoes in Galicia (Northwest Spain) - María Isabel Silva-Torres; Yasmina Martínez-Barciela; Alejandro Polina González; Jose Manuel Pereira Martínez; Ánxela Pousa Ortega; Josefina Garrido González; Rita Sánchez-Andrade; María Sol Arias-Vázquez (Journal of Parasitology Research)
Three females of Coquillettidia richiardii (Ficalbi, 1889) and one female of Culex perexiguus Theobald, 1903/Culex univitattus Theobald, 1901, were recorded for the first time in Galicia (Northwest Spain) during entomological surveillance carried out by the regional vector surveillance network (ReGaViVec) between 2018 and 2022. The specimens were collected from a livestock farm in a Csa (hot Mediterranean summer) climatic zone and a private yard in a Csb (warm Mediterranean summer) climatic zone, according to the Köppen classification. Both species are recognized vectors of pathogens with medical and veterinary implications, underscoring the importance of recording their presence. This study documents their distribution in the region, examines the factors contributing to their detection, and highlights the need for ongoing and systematic vector surveillance.